Home Security : The Keys to the Kingdom (Chip Taylor Communications, 2005)
Shakira is locked out of her house, she wonders how the idea of locking things up got started. Sam and Jen transport Shakira through the ages to provide answers to her questions. First stop, 40,000 years ago to meet two imaginary Paleolithic people who built the first known fence. Second,the Iron Age, when people started to stake out territories. Third, the 1200s when castles were constructed as the first line of defense. Sam and Jen show how laying siege to a castle was very difficult. See how protection gear for today's athletes dates back to armor worn by medieval warriors. Learn how gunpowder led to cannons, guns, and rifles. In the end Shakira discovers things are a little simpler these days.